Dampak Sekuritisasi Konflik Laut Cina Selatan terhadap Keamanan Maritim Indonesia - Sunoto, Suyud Puguh; Fahriani, Ade Aryanti; Napang, Marthen (UI Scholars Hub, 2023)
This study delves into the impact of the securitization of the South China Sea conflict on Indonesia's maritime security, with a focus on the geopolitical challenges faced by the country. National security encompasses not only military aspects but also involves non-traditional threats such as territorial conflicts, economic security, and regional stability. Drawing upon the Copenhagen School of Security Studies, this research considers threats from a liberal perspective, identifying international relations practices that emphasize cooperation and peace. This paper discusses the securitization of the conflict in the South China Sea and its implications for Indonesia's maritime security. By analyzing securitization efforts, this paper identifies the challenges faced by Indonesia and strategies that can be applied to secure national maritime interests amidst regional tensions. The research methodology is descriptive with a qualitative and multidisciplinary approach, using literature review as a data collection technique. Data analysis encompasses Indonesia's national interests, particularly in the context of security, economy, and regional stability. The research findings reveal that the South China Sea conflict has serious implications for Indonesia's maritime security, such as increased defense budgets, trade uncertainty, and political stability. Additionally, Indonesia faces challenges in the form of threats from issues such as terrorism, piracy, illegal fishing, and transnational crime. To address these challenges, the research outlines Indonesia's maritime defense strategies, including diplomatic policies, military capability enhancement, and regional cooperation. Considering the impacts and challenges faced, this research provides crucial insights for policymakers to develop effective measures to safeguard maritime security and national sovereignty amidst the dynamics of global geopolitics.